Expanding Market Access Through the Implementation of Digital marketing in MSME Businesses Bank BTPN Syariah Customers: Perluasan Akses Pasar Melalui Penerapan Digital marketing Pada Usaha UMKM Nasabah Bank BTPN Syariah - Dwi Zhaafira Pratiwi; Dhani Ichsanuddin Nur (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy, contributing significantly to GDP and employment. However, MSMEs face challenges such as limited access to larger markets and capital, necessitating more intensive empowerment efforts. Empowering MSMEs through digital marketing strategies has become an effective solution to enhance competitiveness and business sustainability. Digital marketing offers various tools and platforms that enable MSMEs to reach consumers more broadly and efficiently. This study aims to explore the impact of empowering MSMEs through the implementation of digital marketing on improving business performance. The research method used is a case study of several MSMEs in Indonesia that have successfully adopted digital marketing. The research results show that MSMEs empowered with digital marketing strategies experience significant increases in sales, brand awareness, and access to international markets. These findings indicate that digital marketing is not only a marketing tool but also an empowerment strategy capable of supporting the growth and development of MSMEs in the digital era.